Oleogels for development of health-promoting food products - Martins, Artur J. (2020)
Metabolic health and maintenance of good levels of triglycerides, high-density lipoprotein cholesterol, blood pressure and sugar are concerns to human quality of life. Healthy-driven consumers demand joint with technological innovations, can lead to a diversification of the once stable and strict food industrial output. The fostering of of-the-shelf available, affordable and healthy food products is indeed necessary. Detrimental effects on human health as consequence of the ingestion of saturated fat sources, urges the efforts to find alternatives. Oleogels are interesting structures, which can be tailored with the certain triglycerides and structurants, that can be selected to provide specific fatty acids, target higher levels of cholesterol with competing binding-molecules (e.g. phytosterols), reduce saturated fat content, lessen appetite (by modelling the shape of foods) or carry exclusive bioactives to be absorbed in the digestive tract. Oleogelsâ versatility, easy processing and affordability, is foreseen as an important technological advance in food science. This review explores the strategies in place to develop and produce oleogels, to be introduced in foods and how they might represent an important source of functionality through healthy molecules. Is also explored in what way oleogels can act on the human overall metabolic health, today and in the future.